Ludzka wola Chrystusa w ujęciu teologów kapadockich IV wieku - Kashchuk, Oleksandr (Vox Patrum, 2025)
The article is dedicated to the issue of Christ’s human will in the thought of the Cappadocian theologians of the fourth century, in the context of the early Christian development of the doctrine of Christ’s natures. Its aim is to highlight the role and significance of Christ’s human will in the Christology of Basil the Great, Gregory of Nazianzus, and Gregory of Nyssa. All three thinkers emphasized the fullness of Christ’s humanity, and each of them, to some extent, signaled or drew attention to the existence and function of His human will. The reflection of the Cappadocian theologians was a significant step in the development of Christology, laying the foundations for the teaching that Christ, as a true man, had to possess an authentic human will, which remained in perfect harmony with His divine will. This concept influenced further theological debates and played a crucial role in the later formulation of the doctrine of two wills in Christ in Byzantium in the seventh century.